The effect of logistic controlling on business processes - Méhesné Berek, Szilvia (Applied Studies in Agribusiness and Commerce, 2014)
The increase in the significance of logistics can be attributed to two major reasons: the increasing cost sensitivity of companies and the necessity for the higher fulfilment of customer needs. Logistic controlling is a tool of management used to coordinate logistic activities and to reach logistic managerial decisions by providing information through the analysis of the system. The up-to-date and precise information that can be gained from the logistic controlling system helps the management in the preparation of decisions, and the adaptation to environmental conditions. With these activities, logistic controlling makes the enterprises more efficient and successful. Taking the above into consideration, I carried out a survey on why commercial entities decided on the introduction and application of a logistic controlling system, what conditions are necessary for the introduction of a logistic controlling system, and what experiences the users gained by the application. Positive effects of logistic controlling were proved on operations, and the introduction and application of logistic controlling were analysed.